2022
DOI: 10.1590/0102-311xen095122
|View full text |Cite
|
Sign up to set email alerts
|

Measles outbreaks during the COVID-19 pandemic: medico-legal and public health implications

Abstract: The editorial by Werneck 1 highlighted the weaknesses of health systems in relation to the COVID-19 pandemic. We wanted to draw attention to a very topical problem which, in our opinion, is directly related to damages to health systems caused by the COVID-19 pandemic.In 2021, it became clear that a major problem of the COVID-19 pandemic was the progressive and uncontrolled decrease of children's routine vaccinations 2 . In particular, a worrying reduction in vaccination coverage has been recorded in developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A joint report published in November 2022 by the WHO and the Center for Disease Control (CDC) revealed that many children missed their measles vaccines. Many factors may contribute to this, but the primary one is the COVID-19 pandemic [1] [2]. In 2021 alone, 9 million measles cases and 128000 deaths were reported globally due to significantly declined measles vaccinations and weakened measles surveillance procedures due to COVID-19 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A joint report published in November 2022 by the WHO and the Center for Disease Control (CDC) revealed that many children missed their measles vaccines. Many factors may contribute to this, but the primary one is the COVID-19 pandemic [1] [2]. In 2021 alone, 9 million measles cases and 128000 deaths were reported globally due to significantly declined measles vaccinations and weakened measles surveillance procedures due to COVID-19 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Many factors may contribute to this, but the primary one is the COVID-19 pandemic [1] [2]. In 2021 alone, 9 million measles cases and 128000 deaths were reported globally due to significantly declined measles vaccinations and weakened measles surveillance procedures due to COVID-19 1 . This has caused persistent measles outbreaks in 2022 across the globe and the WHO has stated this as an "imminent threat."…”
Section: Introductionmentioning
confidence: 99%
“…Cioffi & Cecannecchia 13 highlight the significance of financing and strengthening health systems to deal with the disruption caused by the COVID-19 pandemic. This is undoubtedly true, but mitigation and recovery strategies should also consider that, although the COVID-19 pandemic is certainly a significant driver of health disruption, it cannot be fully accountable for all post-pandemic health problems.…”
mentioning
confidence: 99%
“…Another interesting question raised by Cioffi & Cecannecchia 13 is the possibility of considering the governments responsible for the negative outcomes since some effects of the pandemic could be predicted and avoided. Indeed, the catastrophic response of the Brazilian Federal Government to the COVID-19 pandemic was characterized by misguided actions and deliberate inactions 20 .…”
mentioning
confidence: 99%